Percutaneous Coronary Interventions in Patients with ST-segment Elevation Myocardial Infarction and Totally Occluded Culprit Artery after Pre-hospital Thrombolysis - Ivan Bessonov (International Journal of Biomedicine, 2018)
The aim of this study was to evaluate in-hospital outcomes of percutaneous coronary intervention (PCI) in patients with acute STEMI with completely occluded culprit artery after pre-hospital thrombolysis (PT). Methods: Altogether 1,103 consecutive patients with STEMI admitted to the coronary care unit and submitted to PCI from January 2005 to January 2015 were included in the analysis. The clinical and angiographic characteristics, in-hospital outcomes, as well as predictors of no-reflow phenomenon were analyzed. Results: Altogether 708 patients (64.2%) with a completely occluded culprit artery (initial TIMI flow ≤ 1) were included in the analysis. Overall, 78(11%) patients who received PCI after PT (PT-group) were compared with 630(89%) patients who received primary PCI (PPCI-group). The rates of no-reflow (14.1% vs 6.8%; P=0.02) and recurrent MI (5.1% vs 1.3%; P=0.03) were significantly higher in the PT-group. The rates of death (5.2% vs 5.1%; P=0.61) and stent thrombosis (3.8% vs 1.3%; P=0.11), as well as MACE (9.0% vs 7.0%; P=0.52), were comparable between the groups. After univariate analysis, several clinical and procedural characteristics were associated with no-reflow, but only PT was associated with recurrent MI (OR=4.20; 95% CI 1.24-14.3; P=0.02). After multivariate analysis, PT remained an independent predictor of no-reflow (OR=2.53; 95% CI 1.17-5.46; P=0.015) Conclusion: PCI in patients with STEMI and completely occluded culprit artery after PT was associated with higher levels of no-reflow and recurrent MI. Completely occluded culprit artery after PT was an independent predictor of no-reflow during PCI.